Clinical characteristics of Campylobacter enteritis after pediatric renal transplantation: A retrospective analysis from single center. Issue 2 (4th January 2019) - Ban, Hideki; Miura, Kenichiro; Ishizuka, Kiyonobu; Kaneko, Naoto; Taniguchi, Yohei; Nagasawa, Takeshi; Shirai, Yoko; Yabuuchi, Tomoo; Takagi, Yoko; Goto, Aeko; Hattori, Motoshi
Abstract: Background: There are few reports of patients with Campylobacter enteritis after renal transplantation, and only a few case reports of bacteremia have been published. Although antibiotic therapy for 3‐5 days has been recommended for immunocompromised patients, the optimal treatment for Campylobacter enteritis after renal transplantation has not been established. This study aimed to clarify the clinical characteristics and treatment outcomes of Campylobacter enteritis after pediatric renal transplantation. Methods: This retrospective study included patients who underwent pediatric renal transplantation and were found to have Campylobacter species in stool cultures between January 2014 and May 2017. Results: This study included eight patients who underwent pediatric renal transplantation. The median age at the time of renal transplantation was 14 years, and the median period between transplantation and disease occurrence was 4.6 years. Clinical symptoms were abdominal pain for eight patients, diarrhea for eight patients, fever for seven patients, vomiting for three patients, and headache for three patients. Campylobacter jejuni was isolated from the stool cultures of all patients. The median administration period of antibiotics as initial therapy was 7 days (range, 4‐11 days). However, clinical relapse was observed in four patients after completing antibiotic therapy. Patients who experienced clinical relapse required a second course of antibiotic therapy for a median duration of 7 days (range, 5‐10 days). Conclusions: Patients with Campylobacter enteritis after pediatric renal transplantation are at high risk for clinical relapse and may require a longer duration of antibiotic therapy than that generally described.